Dog Bites and Rabies in the Eastern Region of Ghana in 2013–2015: A Call for a One-Health Approach - Boakye-Yiadom Adomako; Frank Baiden; Samuel Sackey; Donne Kofi Ameme; Fred Wurapa; Kofi Mensah Nyarko; Ernest Kenu; Edwin Afari (Journal of Tropical Medicine)
Background. A One-Health approach is advocated to ensure effective rabies surveillance in sub-Saharan Africa. Information is needed to assess the current state of dog bites and rabies in Ghana. We analyzed data on reported events in the Eastern Region of Ghana from 2013 to 2015 to generate information that can be used for rabies elimination in Ghana through the One-Health approach. Method. We extracted data on dog bites and rabies from the database of the regional health service and performed descriptive analysis using Epi Info version 7™. We followed up with interviews with three key informants from the health and veterinary services on issues related to surveillance and data quality. Results. Overall, 4821 dog bites were reported over the three-year period. This translated into an annual incidence of 172 cases per a population of 100,000. Most of cases were in children aged less than 10 yrs. Fifteen (53.3% males) cases of rabies were recorded in seven out of the 26 municipalities and districts, translating into a rabies to dog bite ratio of 3: 1000. The median age of victims was 9 years (range: 3-72 years). A parallel and uncoordinated system of rabies surveillance is maintained by the health and veterinary services, with gross disparities in the number of reported events and overall impression of underreporting. Conclusion. Rabies remains an important cause of preventable deaths in this region. An integrated approach to surveillance based on the One-Health concept needs to be adopted.